Parameters determining micromotion at the implant-abutment interface - Karl, Matthias; Taylor, Thomas D. (International Journal of Oral & Maxillofacial Implants, 2014)
Micromotion at the implant-abutment level has been reported to be a major determinant of longterm implant success, as technical problems ranging from screw loosening to screw fracture may occur as a consequence of excessive micromotion.Following published standards, implant-abutment assemblies were fixed in a universal testing machine at a 30-degree angle. A cyclic load of 200 N was applied to the specimens 10 times at a crosshead speed of 100 N/s while relative displacement between the implant and the abutment was quantified using extensometers. For five consecutive loading cycles per specimen, micromotion was recorded as a basis for statistical analysis, with two-sample t tests (Welch test) applied.Micromotion at the implant-abutment interface ranged from 1.52 to 94.00 ?m. While a significant effect of tightening torque was found, implant shoulder design did not reveal a significant effect in all cases. Lack of engagement of antirotational features of the implants resulted in increased micromotion. Casting onto prefabricated gold cylinders resulted in abutments with significantly less micromotion as compared to copy-milled and stock abutments. Computer-aided design/computer-assisted manufacture (CAD/CAM) zirconia abutments showed less micromotion than CAD/CAM titanium abutments. Inconsistent levels of micromotion were recorded for CAD/CAM abutments coupled to proprietary and competing implant systems. Great variations in micromotion were found with clone abutments and clone implant systems.A broad range of micromotion values was observed with the implant abutment combinations investigated. There seems to be no perfect implant shoulder geometry or perfect fabrication technique that would result in no detectable micromotion.
EVALuna2:24818